Taxes. - Hunsaker, L. Don; Kesselman, Jerome J. (The Accounting Review, 1957)
Reviews two books on taxation. "Federal Income Taxation of farmers," by Harry M. Halstead; "The Tax on Accumulated Earnings," by Robert S. Holzman.